2012
DOI: 10.1111/j.1478-3231.2012.02762.x
|View full text |Cite
|
Sign up to set email alerts
|

Blockage of the afferent sensitive pathway prevents sympathetic atrophy and hemodynamic alterations in rat portal hypertension

Abstract: These results indicate that the nervous system has a central role in the genesis of the circulatory abnormalities of portal hypertension, and support that mesenteric sympathetic atrophy contributes to splanchnic arterial vasodilation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 33 publications
4
16
0
1
Order By: Relevance
“…6 G and H) and p75 neurotrophin receptor (i.e., reduced neurite sprouting) in DH laminae I-III (Fig. 6 K and L), both of which are largely dependent on neuronal activity (43). Likewise, HUP-A-mediated postsynaptic inhibition (44) may be responsible for the observed down-regulation of the CRLR and the NK1R in DH sensory neurons (Fig.…”
Section: Discussionmentioning
confidence: 93%
“…6 G and H) and p75 neurotrophin receptor (i.e., reduced neurite sprouting) in DH laminae I-III (Fig. 6 K and L), both of which are largely dependent on neuronal activity (43). Likewise, HUP-A-mediated postsynaptic inhibition (44) may be responsible for the observed down-regulation of the CRLR and the NK1R in DH sensory neurons (Fig.…”
Section: Discussionmentioning
confidence: 93%
“…However, recent reports suggest splanchnic sympathetic atrophy in portal hypertension. In detail, marked reduction of sympathetic nerves and decreased protein expression of tyrosine-hydroxylase key enzyme for NA synthesis have been demonstrated in portal hypertensive mesenteric arteries [10][11][12]. Applying a model of repetitive electric PNS resembling sustained splanchnic vascular SNS activity, we report that cirrhotic rats display almost doubled and about 30% increased NA release caused by first and subsequent PNS, respectively.…”
Section: Discussionmentioning
confidence: 93%
“…Es gibt deutliche Evidenz dafür, dass bei portaler Hypertension die systemischen NA-Plasmakonzentrationen hauptsächlich von der mesenterialen NA-Produktion abhängen [5]. Aber anders als bei systemischen NAKonzentrationen sind Daten zu lokaler splanchnischer Neurotransmitter-Produktion und -Sekretion sehr spärlich vorhanden und zudem kontrovers [6][7][8][9][10][11][12].…”
Section: Dysbalance In Sympathetic Neurotransmitter Release and Actiounclassified
See 1 more Smart Citation
“…It has also been proposed that during portal hypertension, pressure changes detected at portal level could be the afferent sensory signal triggering this hemodynamic response [5]. We have demonstrated that blockade of sensory afferent nerves in portal hypertensive rats, simultaneously prevents c-fos activation in cardiovascular regulatory nuclei of the brain, hemodynamic alterations and sympathetic atrophy of nerves innervating the superior mesenteric artery (SMA) [6][8].…”
Section: Introductionmentioning
confidence: 92%